Regional cumulative maximum dose to the spinal cord in head-and-neck cancer: considerations for re-irradiation - Stoiber, Eva Maria; Debus, Jürgen; Huber, Peter E.; Bendl, Rolf; Giske, Kristina (Radiotherapy and oncology, 2013)
Purpose To present a new method that assesses the delivered maximum dose of different spinal cord sections in head-and-neck cancer treated with intensity-modulated radiation therapy (IMRT). This allows a more accurate estimation of the remaining cord dose tolerance in case of a later re-irradiation treatment planning. Materials and methods The suggested workflow is demonstrated using daily acquired kilo-voltage control-CTs of four head-and-neck cancer patients (118 control-CTs). The local maximum dose inside different cord levels is determined and accumulated for the planning situation and over the treatment course for an IGRT and a non-IGRT approach. Results The approach is suitable to accurately detect and document the delivered maximum dose dependent on the cord levels. The delivered maximum dose differed up to 13% from the planned one in all sections due to setup uncertainties and the applied correction strategy. Conclusion The presented approach facilitates later re-irradiation treatment planning due to detailed documentation of the delivered maximum dose to the spinal cord levels in the primary IMRT. The method also facilitates the interpretation of complex 3D dose information by reducing it to its essentials. This 2D illustration is an aid to orientation for the physician in the re-irradiation planning process.
Available online 20 December 2012
Gesehen am 28.08.2020